Determinants of influenza vaccination among solid organ transplant recipients attending Sicilian reference center. Issue 2 (1st February 2017) - Restivo, Vincenzo; Vizzini, Giovanni; Mularoni, Alessandra; Di Benedetto, Cinzia; Gioè, Santi Mauro; Vitale, Francesco
ABSTRACT: Among solid organ transplant recipients, influenza infection is commonly associated with higher morbidity and mortality than immunocompetent hosts. Therefore, in these subjects influenza vaccination is of paramount importance. The main objective of the study was to assess compliance to vaccination and analyze factors associated with influenza vaccination of solid organ transplant recipients admitted to the Sicilian solid organ transplant Reference Center IRCCS-ISMETT in Palermo during 2014–2015 influenza season. Thirty one (37.8%) out of 82 solid organ transplant recipients were vaccinated against influenza. The main reason for vaccination refusal was fear of adverse reaction (n = 16, 31.4%), impaired health status (n = 14, 27.4%) and low vaccine efficacy (n = 10, 19.6%). Vaccinated solid organ transplant recipients compare with unvaccinated had smaller hospital admissions for infectious respiratory diseases (9.7% Vs 23.5%) during surveillance period. On multivariate analysis the factors positively associated with influenza vaccination were the advice of Reference Center physicians (OR 53.4, p < 0.001) and to perform vaccine against pneumococcus (OR 7.0, p = 0.016). This study showed that Reference Center physicians play a key role on vaccine communication and recommendation for patients at risk and it underlines the effectiveness of influenza vaccination in solid organ transplant recipients. However, it remains that, although physician advice resulted a strong determinant for vaccination, influenza vaccination coverage in this subset of population remains still unsatisfactory.